Memory Effects of Benzodiazepines: Memory Stages and Types Versus Binding-Site Subtypes - Miroslav M. Savic; Dragan I. Obradovic; Nenad D. Ugrešic; Dubravko R. Bokonjic (Neural Plasticity)
Benzodiazepines are well established as inhibitory modulators of memory processing. This effect is especially prominent when applied before the acquisition phase of a memory task. This minireview concentrates on the putative subtype selectivity of the acquisition-impairing action of benzodiazepines. Namely, recent genetic studies and standard behavioral tests employing subtype-selective ligands pointed to the predominant involvement of two subtypes of benzodiazepine binding sites in memory modulation. Explicit memory learning seems to be affected through the GABAA receptors containing the α1 and α5 subunits, whereas the effects on procedural memory can be mainly mediated by the α1 subunit. The pervading involvement of the α1 subunit in memory modulation is not at all unexpected because this subunit is the major subtype, present in 60% of all GABAA receptors. On the other hand, the role of α5 subunits, mainly expressed in the hippocampus, in modulating distinct forms of memory gives promise of selective pharmacological coping with certain memory deficit states.